Analysis of base sector and non-base sector on economic growth in Pagar Alam city - Pasandi, M. Ramadhan; Subardin, Muhammad (Universitas Ahmad Dahlan, 2025)
This study aims to examine the effect of the base sector and non-base sector on economic growth in Pagar Alam City, using time-series data from 2010 to 2022. The study employs Static Location Quotient (SLQ) and Dynamic Location Quotient (DLQ) analyses, followed by typology klassen analysis, to identify both base and non-base sectors. This study also uses multiple linear regression to estimate how different sectors influence economic growth. The gap of research is analyze in detail in combining these methods to evaluate sectoral impacts in Pagar Alam, a highland city with significant untapped potential. The result show that key sectors like agriculture, construction, and education play a crucial role in driving economic growth in Pagar Alam city, while non-key sectors tend to have a weaker or even negative impact. The implication of the study government should ensure the sustainability of Pagar Alam's agriculture, forestry, and fisheries sectors, which are vital to the local economy and tourism.